A study of visceral adiposity index as a diagnostic index in gestational diabetes mellitus in a tertiary care centre - Dakshnamurthy, Padmalatha; Thangiah Kasirajan, Shaanthy Gunasingh; Nachiyar, Indhumathi; Geetha, Mangala; Rajendran, Kannan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Gestational Diabetes Mellitus is an emerging problem which affects pregnant women all over the world particularly in India. Early detection reduces adverse maternal and foetal outcome. Elevated central adiposity is a modifiable risk factor for abnormal glucose homeostasis in pregnancy and GDM. The Visceral Adiposity Index (VAI) is a gender-specific index of fat distribution and assessment. Methods: It is a hospital based, case control study among the subjects who attended a tertiary care centre. cases were 30 pregnant women newly diagnosed with GDM in their 2nd trimester, and Controls were 30 apparently healthy pregnant women in their 2nd trimester without risk factors for GDM such as obesity and family history for diabetes. Visceral Adiposity Index (VAI) was calculated using the formula (Waist circumference (WC)/ {36.58 +(1.89xBMI)}) x(TGL/0.81) x (1.52/HDL) where WC is expressed in cm, BMI in Kg/m2, TG in mmol/L, HDL in mmol/L. Results: The mean age of patients with GDM was higher when compared to controls (28.17 ± 3.34vs 24.40±3.07) and this difference was statistically significant (p value < 0.0001). The average weights were significantly different. The mean Body Mass Index (BMI) and waist circumference (WC) was 23.59 ± 4.19 and 88.46 ± 7.10 respectively among controls and 29.85 ±4.52 and 102.12 ± 6.96 respectively among GDM patients and these differences were highly significant (p value<0.0001). The lipid profile of these patients showed a significantly higher value of Triglycerides among patients. Conclusions: This study correlates GDM with Visceral adiposity index and found that the index to be elevated in the GDM group. The increased VAI in GDM patients shows their elevated adipose tissue distribution. VAI is less invasive and cost effective, can be used as a diagnostic index in GDM.